2016
DOI: 10.1177/1087054714554933
|View full text |Cite
|
Sign up to set email alerts
|

High IQ May “Mask” the Diagnosis of ADHD by Compensating for Deficits in Executive Functions in Treatment-Naïve Adults With ADHD

Abstract: Adults with ADHD and more elevated IQ show less evidence of executive functioning deficits compared with those with ADHD and standard IQ, suggesting that a higher degree of intellectual efficiency may compensate deficits in executive functions, leading to problems in establishing a precise clinical diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 43 publications
4
32
0
Order By: Relevance
“…16 Other studies suggest that IQ is distributed normally within the ADHD population, and that it can be a predictor of better performance and later medical evaluation. [17][18][19] A recent neuroimaging study 20 demonstrated that the co-occurrence of ADHD and high IQ has a different neuroanatomical behavior then the other types (ADHD with normal IQ and ADHD with low IQ). 2 While IQ correlated positively with gray matter volume (r = 0.31) in controls, in the ADHD/high-IQ group, this correlation was negative (r = -0.25).…”
mentioning
confidence: 99%
“…16 Other studies suggest that IQ is distributed normally within the ADHD population, and that it can be a predictor of better performance and later medical evaluation. [17][18][19] A recent neuroimaging study 20 demonstrated that the co-occurrence of ADHD and high IQ has a different neuroanatomical behavior then the other types (ADHD with normal IQ and ADHD with low IQ). 2 While IQ correlated positively with gray matter volume (r = 0.31) in controls, in the ADHD/high-IQ group, this correlation was negative (r = -0.25).…”
mentioning
confidence: 99%
“…For assessing AD, a Stroop test was performed, which is commonly used for evaluating selective attention, cognitive flexibility, and inhibitory control . Also, it is used for discrimination of individuals with ADHD and without ADHD .…”
Section: Methodsmentioning
confidence: 99%
“…Finally, it has been argued that the cognitive correlates of highly intelligent individuals with ADHD are similar in type and severity as those in average intelligent individuals with ADHD [7,20] but are easily overlooked when compared to typical (i.e., average intelligent) controls [2]. According to this hypothesis, when ADHD and high intelligence occur together, the high intelligence may compensate/mask the ADHD-related impairments [16,[20][21][22][23]. As a consequence, the cognitive correlates of ADHD in highly intelligent individuals are only observed when compared to highly intelligent controls, yet not when compared to average intelligent controls ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1c: "compensating-hypothesis"). ADHD-related problems (such as underachievement at school) may thus be easily overlooked when compared to the typical (average intelligent) classmate [2,23].…”
Section: Introductionmentioning
confidence: 99%